2023
DOI: 10.1177/24730114221151079
|View full text |Cite
|
Sign up to set email alerts
|

Advancements in Artificial Intelligence for Foot and Ankle Surgery: A Systematic Review

Abstract: Background: There has been a rapid increase in research applying artificial intelligence (AI) to various subspecialties of orthopaedic surgery, including foot and ankle surgery. The purpose of this systematic review is to (1) characterize the topics and objectives of studies using AI in foot and ankle surgery, (2) evaluate the performance of their models, and (3) evaluate their validity (internal or external validation). Methods: A systematic literature review was conducted using PubMed/MEDLINE and Embase data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…Merrill et al 14 internally validated these approaches and found both models to perform similarly, with areas under the curves for logistic regression ranging from 0.7101 to 0.7583 and areas under the curves for gradient boosting ranging from 0.6979 to 0.7580. A recent systematic review by Gupta et al 7 provides an overview of 31 studies related to the use of AI in foot and ankle surgery and is an excellent resource for surgeons interested in learning about the capabilities of AI in our feild.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Merrill et al 14 internally validated these approaches and found both models to perform similarly, with areas under the curves for logistic regression ranging from 0.7101 to 0.7583 and areas under the curves for gradient boosting ranging from 0.6979 to 0.7580. A recent systematic review by Gupta et al 7 provides an overview of 31 studies related to the use of AI in foot and ankle surgery and is an excellent resource for surgeons interested in learning about the capabilities of AI in our feild.…”
Section: Discussionmentioning
confidence: 99%
“…The use of artificial intelligence (AI) methodologies for various applications in orthopaedic foot and ankle surgery is growing. 3,[7][8][9][10]24 ChatGPT (Generative Pretrained Transformer) (Open AI, San Francisco, CA) was launched by OpenAI on November 30, 2022, and is a generative language model tool with the capacity to enable the public to converse with an AI network utilizing a text-based platform. Early in 2023, ChatGPT was the fastest-growing consumer application to date, reaching more than 100 million users.…”
Section: Introductionmentioning
confidence: 99%
“…This review highlights the remarkable achievements of artificial intelligence models in various tasks, such as fracture recognition, evaluating surgical suitability, and predicting surgical outcomes. A recent survey [26] underscores that the majority of current studies in this domain revolve around AI applications for imaging analysis, with a particular focus on fracture identification and classification. For a more comprehensive exploration of AI applications in foot and ankle surgery, interested readers are encouraged to consult [24][25][26] and the references cited therein.…”
Section: Problem Statementmentioning
confidence: 99%
“…A recent survey [26] underscores that the majority of current studies in this domain revolve around AI applications for imaging analysis, with a particular focus on fracture identification and classification. For a more comprehensive exploration of AI applications in foot and ankle surgery, interested readers are encouraged to consult [24][25][26] and the references cited therein.…”
Section: Problem Statementmentioning
confidence: 99%